Guiding Myocardial Revascularization by Algorithmic Interpretation of FFR Pullback Curves: A Proof of Concept Study - Argacha, Jean-François; Decamp, Jean; Vandeloo, Bert; Babin, Danilo; Lochy, Stijn; Van den Bussche, Karen; de Hemptinne, Quentin; Xaplanteris, Panagiotis; Magne, Julien; Segers, Patrick; Cosyns, Bernard (Frontiers in Cardiovascular Medicine, 2021)
Background: Coronary artery disease distribution along the vessel is a main determinant of FFR improvement after PCI. Identifying focal from diffuse disease from visual inspections of coronary angiogram (CA) and FFR pullback (FFR-PB) are operator-dependent. Computer science may standardize interpretations of such curves. Methods: A virtual stenting algorithm (VSA) was developed to perform an automated FFR-PB curve analysis. A survey analysis of the evaluations of 39 vessels with intermediate disease on CA and a distal FFR <0.8, rated by 5 interventional cardiologists, was performed. Vessel disease distribution and PCI strategy were successively rated based on CA and distal FFR (CA); CA and FFR-PB curve (CA/FFR-PB); and CA and VSA (CA/VSA). Inter-rater reliability was assessed using Fleiss kappa and an agreement analysis of CA/VSA rating with both algorithmic and human evaluation (operator) was performed. We hypothesize that VSA would increase rater agreement in interpretation of epicardial disease distribution and subsequent evaluation of PCI eligibility. Trial registration: https://www.clinicaltrials.gov/ct2/show/NCT03824600 Results: Inter-rater reliability in vessel disease assessment by CA, CA/FFR-PB and CA/VSA were respectively 0.32 (95%CI:0.17-0.47), 0.38 (95%CI:0.23-0.53) and 0.4 (95%CI:0.25-0.55). The raters' overall agreement in vessel disease distribution and PCI eligibility was higher with the VSA than with the operator (respectively 67 vs. 42%, and 80 vs. 70%, both p<0.05). Compared to CA/FFR-PB, CA/VSA induced more reclassification towards a focal disease (92 vs. 56.2%, p<0.01) with a trend towards more reclassification as eligible for PCI (70.6 vs. 33%, p=0.06). Change in PCI strategy did not differ between CA/FFR-PB and CA/VSA (23.6 vs. 28.5%, p=0.38). Conclusions: VSA is a new program to facilitate and standardize the FFR pullback curves analysis. When expert reviewers integrate VSA data, their assessments are less variable which might help to standardize PCI eligibility and strategy evaluations.